2005
DOI: 10.1002/ana.20378
|View full text |Cite
|
Sign up to set email alerts
|

Bone mass and turnover in women with epilepsy on antiepileptic drug monotherapy

Abstract: Antiepileptic drugs, particularly cytochrome P450 enzyme inducers, are associated with disorders of bone metabolism. We studied premenopausal women with epilepsy receiving antiepileptic drug monotherapy (phenytoin, carbamazepine, valproate, and lamotrigine). Subjects completed exercise and nutrition questionnaires and bone mineral density studies. Serum was analyzed for indices of bone metabolism including calcium, 25-hydroxyvitamin D, parathyroid hormone, insulin growth factor I, insulin binding protein III, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
110
2
11

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(132 citation statements)
references
References 36 publications
(49 reference statements)
7
110
2
11
Order By: Relevance
“…These include the risk of drug interactions with comedications frequently taken by elderly patients Perucca, 2003a, 2003b), and adverse effects on endocrine function and bone mineralization . Because of its lack of enzyme-inducing effects, LTG may be preferable to CBZ in minimizing these concerns (Morrell, 2003;Pack et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…These include the risk of drug interactions with comedications frequently taken by elderly patients Perucca, 2003a, 2003b), and adverse effects on endocrine function and bone mineralization . Because of its lack of enzyme-inducing effects, LTG may be preferable to CBZ in minimizing these concerns (Morrell, 2003;Pack et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In their study, an increase in markers of bone turnover was seen after 2 years, but vitamin D metabolism was normal in all pubertal stage groups. In contrast, 2 other studies have failed to find an association between carbamazepine and altered bone turnover (15,26 One of the limitations of the present study is the cross-sectional nature, where BMD was measure only once, turning it difficult to know if the low bone density observed in the patients group is specifically related to AEDs use. However, by the fact that other secondary causes were excluded and the patients presented lower BMD than the control matched group, we do believe that the use of AEDs may play a role on this issue.…”
Section: Patients Exposedmentioning
confidence: 58%
“…Other drugs that are not enzyme inducers, such as sodium valproate, may exert indirect effects on bone metabolism by altering renal function (12). In addition, it has been reported that AEDs lead to an increase in bone turnover, as demonstrated by elevated levels of bone turnover markers (13)(14)(15)(16).…”
mentioning
confidence: 99%
“…In 40% of epileptic patients the fracture is associated with osteopenia, which is either due to physical impairment, postmenopausal state, or related to anti-epileptic drugs (AED) [4,5]. by altering osteoblastic function, may affect intestinal calcium absorption and can induce anticonvulsant osteopathy [15][16][17]. Our patient did not use any AEDs.…”
Section: Discussionmentioning
confidence: 83%